Cost evaluations in health professions education: a systematic review of methods and reporting quality. Issue 12 (11th August 2019) - Foo, Jonathan; Cook, David A; Walsh, Kieran; Golub, Robert; Abdalla, Mohamed Elhassan; Ilic, Dragan; Maloney, Stephen
Abstract : Context: High‐quality research into education costs can inform better decision making. Improvements to cost research can be guided by information about the research questions, methods and reporting of studies evaluating costs in health professions education (HPE). Our objective was to appraise the overall state of the field and evaluate temporal trends in the methods and reporting quality of cost evaluations in HPE research. Methods: We searched the MEDLINE, CINAHL (Cumulative Index to Nursing and Allied Health Literature), EMBASE, Business Source Complete and ERIC (Education Resources Information Centre) databases on 31 July 2017. To evaluate trends over time, we sampled research reports at 5‐year intervals (2001, 2006, 2011 and 2016). All original research studies in HPE that reported a cost outcome were included. The Medical Education Research Study Quality Instrument (MERSQI) and the BMJ economic checklist were used to appraise methodological and reporting quality, respectively. Trends in quality over time were analysed. Results: A total of 78 studies were included, of which 16 were published in 2001, 15 in 2006, 20 in 2011 and 27 in 2016. The region most commonly represented was the USA ( n  = 43). The profession most commonly referred to was that of the physician ( n  = 46). The mean ± standard deviation (SD) MERSQI score was 10.9 ± 2.6 out of 18, with no significant change over time (p = 0.55). The mean ± SD BMJ score was 13.5 ± 7.1 out of 35, with no significant change over time (p = 0.39). A total of 49 (63%) studies stated a cost‐related research question, 23 (29%) stated the type of cost evaluation used, and 31 (40%) described the method of estimating resource quantities and unit costs. A total of 16 studies compared two or more interventions and reported both cost and learning outcomes. Conclusions: The absolute number of cost evaluations in HPE is increasing. However, there are shortcomings in the quality of methodology and reporting, and these are not improving over time. Abstract : Cost may be most influential yet least studied determinant of practice in health professional education. In this systematic review, Foo et al. explore the state of the literature regarding formal use of cost‐evaluations.